Questioning the Effectiveness of Procedural Repetition: The Case of Spanish EFL Primary School Learners - Lázaro Ibarrola, Amparo; VILLARREAL OLAIZOLA, IZASKUN (Porta Linguarum An International Journal of Foreign Language Teaching and Learning, 2019)
It has been claimed that the repetition of the same task type with different content, known as procedural repetition (PR), seems to offer opportunities to focus on form and develop syntactic complexity. At the same time, PR is common and deemed appropriate for the language classroom. This quasi-experimental study explores the effects of PR on the overall production of 5 pairs of young Spanish EFL (age 11) learners in a school context with a beginner level of English. The pairs co-constructed and narrated three stories following the same procedure at three testing times over a three-week period. The analysis of the complex-ity, accuracy, and fluency of their narratives shows that, unlike previous studies, PR does not have any significant impact on the students’ performance, except for lexical density, which increases in the third attempt. In light of these results, the validity of PR for child populations is discussed.